From the grassroots to the elites: examining collaboration among local service providers. Issue 1 (1st January 2016) - Hicks, Ashley A.; Wilkinson, Deanna L.; Snyder, Anastasia
Abstract: Multiple agencies with varying missions often coexist within large urban communities. Collaboration among these providers is often encouraged as a means to increase access and quality of services provided to individuals and families. Few studies have examined how agencies with varying goals collaborate within communities to provide multiple services to distressed families and communities. The current study examines this process in a sample of 74 agencies addressing multiple needs in a Midwestern city (USA). Respondent agencies report a large network of partnerships with varying motivations for collaboration. Findings reveal that a hierarchical structure of service delivery partly accounts for patterns of collaboration and service provision among providers.